The interior design reference + specification book - Grimley, Chris; Love, Mimi (Rockport Publishers, 2013)
"The Interior Design Reference & Specification Book collects the information essential to planning and executing interior projects of all shapes and sizes, and distills it in a format that is as easy to use as it is to carry. In this new, revised edition, you'll also find interviews with top practitioners drawn across the field of interior design"--Provided by publisher.